Effect of the change in antiviral therapy indication on identifying significant liver injury among chronic hepatitis B virus infections in the grey zone - Ren, Shan; Wang, Wenjing; Lu, Junfeng; Wang, Kefei; Ma, Lina; Zheng, Yanhong; Zheng, Sujun; Chen, Xinyue (Frontiers in Immunology, 2022)
Objective To investigate the effect of the change in antiviral therapy indication in identifying significant liver injury among chronic hepatitis B virus(HBV) infection in the grey zone(GZ). Methods Chronic HBV infections with persistent normal(UNL:≦40 U/L)ALT level (PNALT), who underwent ultrasonography-guided percutaneous liver biopsy, were examined retrospectively. Complete clinical data, liver inflammation and fibrosis grades were collected, while levels of cytokines were detected by Luminex technique, all of them were analyzed to investigate immune state of liver histopathology. Results Totally, 51.3% of patients were in the GZ phase, 50.1% of all patients presented evidenced hepatic injury (EHI).IL-6 level were higher in EHI than Non-EHI (2.77 vs. 1.53pg/mL, Z=-13.32,P=0.028). MCP-1 level was positively correlated with HBV DNA(R=0.64, P＜0.001) and HBeAg(R=0.5, P＜0.001),while negatively correlated with histological grading of fibrosis (R=-0.26, P=0.048).. The ratio of EHI in the GZ phase was 60.55%, significantly higher than patients in the immune tolerance phase(IT:39.8%) and inactive HBV surface antigen (HBsAg) carriers (IHC:37.7%) (P=0.006). 46.69% of all patients were exceeding new ALT antiviral treatment threshold (30 U/L for men and 19 U/L for women).The EHI in IT and IHC phase within the new ALT threshold was 32.6% and 37.8%, whereas higher EHI of 67.4% and 68.4% were seen in GZ-1 and GZ-2 patients exceeding new ALT threshold, the difference were statistically significant (c2=11.13, P<0.001;c2=14.22, P=0.002).The median age in our cohort was 38.91 years, only 21.03% of patients were<30-years-old. The EHI in the IT and IHC patients less than 30-years-old were 32.4% and 35.8%, while the ratio increased to 43.2% for older than 30 years even in the IT and IHC stage. Conclusion Setting 30-year-old and lowering the ALT threshold could facilitate the screening for the presence of significant liver injury,especially for GZ patients. IL-6 was a good indicator of EHI and MCP-1 was significantly positively correlated with HBV DNA, while negatively correlated with liver fibrosis.